ChemInform Abstract: Synthesis of 1, 3‐Amino Alcohols, 1, 3‐Diols, Amines, and Carboxylic Acids from Terminal Alkynes. Issue 2 (23rd December 2015) - Zeng, Mingshuo; Herzon, Seth B.
Abstract: Anti‐Markovnikov functionalization reactions of terminal alkynes and propargylic amines efficiently lead to 1, 3‐diol products and 1, 3‐amino alcohols, respectively, without loss of stereochemistry.